Contradictions of the plot in Roberto Bolaño’s short stories - Velarde, Luis Alberto (Árboles y Rizomas, 2021)
This article examines the narrative strategies used by Bolaño in those stories marked by a undermining of the plot. The virtuality of the narrative action, the anti-closures, the lyricism and the conjectures are considered as substitutes for the narrative nexus that allow the unity and completeness of the story. Despite the openness, the episodic nature of the actions, the apparent lack of selections from these and the spatiality inherent in lyricism and guesswork, the stories have the characteristic unity of the plot. It is precisely in the characteristics of the plot and the procedures used that Bolaño's aesthetic proposal is evident and the starting point of the interpretation of its meaning as a socially symbolic object. In this sense, the tensions observed in the configuration of the plot in relation to the intelligibility of human action are interpreted, evaluating the pessimism of Bolaño's narrative within the framework of the literary cycle to which it belongs and the descriptions of its production made by critics like Grinor Rojo.
Keywords: plot; narrative time; aesthetics; Bolaño; short story